Editorial Revista Digital do LAV – vol.9, n.1, jan./abr. - Oliveira, Marilda Oliveira de; Charréu, Leonardo (Revista Digital do LAV, 2016)
Revista Digital do LAV – Laboratório de Artes Visuais – vol.9, n.1, jan./abr.